The impact of product quality, service quality, price and location on satisfaction and behavioural intentions in housing industry:the moderating role of delivery systems / Aziam Mustafa - Mustafa, Aziam (2015)
Customer satisfaction is essential for enhancement of competitive advantage in housing industry. Customer satisfaction brings about a lot of positive implications to the companies, which may contribute to a successful business. It is essential to maintain the customers' satisfaction by offering the right product and services that fulfill their needs and expectations. The customer satisfaction and behavioural intentions were studied and comparisons were made between two types of delivery systems; Sell Then Build (STB) and Build Then Sell (BTS) on the relationship between service providers' attributes, satisfaction and behavioural intentions in housing industry. The service providers' attributes are comprised of the product quality, service quality, price and location which refer to the aggregate services provided by the service provider to their buyers. The objectives of this study are threefold: (1) to examine the direct effect of service providers' attributes comprises product quality, service quality, price and location on buyer's satisfaction and behavioural intentions. (2) to examine the role of satisfaction as a mediating variable between product quality, service quality, price and location towards behavioural intentions and (3) to identify the moderating effect of the delivery systems (Sell Then Build and Build Then Sell) on the underlying relationship between product quality, service quality, price and location on buyers' satisfaction and behavioural intentions. A cross-sectional survey was conducted among house buyers in the urban areas in Klang Valley using self-administered questionnaires. The significant effect of product quality, service quality, price and location on buyers' satisfaction and behavioural intentions was tested using Structural Equation Modeling (SEM) procedure. The findings illustrated that only service quality and price have positive relationship with buyers' satisfaction while only price has a significant effect on behavioural intentions. It also revealed that the buyers would recommend and say positive word of mouth about the service providers. Satisfaction was found to mediate the relationship between service quality and price on behavioural intentions while product quality and location were not significant. Both types ofdelivery systems (STB and BTS) in. this study moderate the effect of price and buyers'satisfaction, However, delivery systems (STB or BTS) do not moderate the effect of the independent variables and the behavioural intentions. The findings hold strong implications for governing bodies, industry practitioners and funding agencies as they magnify the need for new and holistic strategies to address buyers' expectations as well as the developers' intensity in developing innovative housing solutions.